Combined spectroscopic studies on post-functionalized Au25 cluster as an ATR-FTIR sensor for cations. Issue 21 (28th April 2021) - Baghdasaryan, Ani; Brun, Elodie; Wang, Yuming; Salassa, Giovanni; Lacour, Jérôme; Bürgi, Thomas
Abstract : Using ligand exchange reactions an atomically precise gold cluster was functionalized with a di-thiolated crown ether. Using in situ infrared spectroscopy films of the resulting composite were shown to incorporate metal cations. Abstract : Recently, significant research activity has been devoted to thiolate-protected gold clusters due to their attractive optical and electronic properties. These properties as well as solubility and stability can be controlled by post-synthetic modification strategies. Herein, the ligand exchange reaction between Au25 (2-PET)18 cluster (where 2-PET is 2-phenylethanethiol) and di-thiolated crown ether ( t -CE) ligands bearing two chromophores was studied. The post-functionalization aimed to endow the cluster with ion binding properties. The exchange reaction was followed in situ by UV-vis, 1 H NMR and HPLC. MALDI mass analysis revealed the incorporation of up to 5 t -CE ligands into the ligand shell. Once functionalized MALDI furthermore showed complexation of sodium ions to the cluster. ATR-FTIR spectroscopic studies using aqueous solutions of K +, Ba 2+, Gd 3+ and Eu 3+ showed noticeable spectral shifts of the C–O stretching band around 1100 cm −1 upon complexation. Further spectral changes point towards a conformational change of the two chromophores that are attached to the crown ether. Density functional theory calculations indicate that the di-thiol ligand bridges two staple units on the cluster. The calculations furthermore reproduce the spectral shift of the C–O stretching vibrations upon complex formation and reveal a conformational change that involves the two chromophores attached to the crown ether. The functionalized clusters have therefore attractive ion sensing properties due to the combination of binding properties, mainly due to the crown ether, and the possibility for signal transduction via an induced conformational change involving chromophore units.